Pertumbuhan dan Faktor Kondisi Ikan Gabus (Chana striata Bloch, 1793) - Sunarni, Sunarni; Elviana, Sisca; Wairara, Stenly Suryani (AGRICOLA, 2021)
This study aims to analyze the growth and condition factors of Snakehead fish (Channa striata Bloch, 1793) caught in the waters of the Wasur swamp, Merauke district. The research was conducted in September-November 2020 in the Wasur swamp waters. The method used is descriptive method with purposive sampling technique. The data analysis used was the long-weight relationship data to determine the growth pattern of snakehead fish and condition factors. The results of the research at the two stations in September and October showed the same growth pattern, namely negative issometric and allometric, while in November station I was allometric negative and station II was issometric. The value of the condition factor at the two stations in September, October and November ranged from 1.003 to 1.006, including in the not fat category.